Meningkatkan Kualitas Pendidikan Anak Usia Dini melalui Pembelajaran Kontekstual dengan Pendekatan Merdeka Belajar - Nisna Nursarofah (Universitas Islam Tribakti Lirboyo Kediri, 2022)
The quality of education in Indonesia still needs to be improved, one of which is in early childhood education institutions. There are problems that occur in education in Indonesia, namely in the implementation of a learning process that is only teacher-oriented which causes children to be less independent in solving a problem and children become less creative. Then teachers who deliver learning only with theory without any learning media so that children do not understand the meaning of what is conveyed. The author uses the literature study research method, and takes data from books, articles, the internet, and other relevant sources of information. The results of the literature review on improving the quality of early childhood education through contextual learning with the MERDEKA BELAJAR approach are expected to be one way to improve the quality of education in Indonesia. The essence of contextual learning with an independent learning approach is learning that connects theory with real life so as to provide more concrete and meaningful learning, and also gives children the freedom to find and solve a problem in the learning process both in groups and individually so as to increase children's independence and creativity.